Modelling rapid urban growth of Kirkuk City based on ethnicity factors using GIS and cellular automata-Markov - Abdula, Mazen Abdilwahab (2016)
During the past 90 years, Kirkuk City has grown rapidly due to the exploitation of its oil reserves. As a multi-ethnic city, the presence of oil has been a source of ethnic conflict among the Kurds, Arabs and Turkmen. Kirkuk has long been considered an ethnic powder keg waiting to explode. Each group’s own distinctive historical narrative became increasingly politicised and antagonistic during the twentieth century. The Iraqi Government implemented an aggressive and extensive social engineering policy designed to manage potential political and security threats to the oilfields that had been established in Kirkuk. A new social policy of Arabisation was implemented; a preferential treatment policy which favoured the ethnic Arabs over non-Arabs. However, while the ethnic Arabs benefitted from the affirmative action policy, the other ethnicities were expelled and this led to rising ethnic tension; planting a seed of antagonism towards ethnic Arabs and led to negative social relations between ethnic groups, which was augmented by residential segregation that divided the three major ethnic groups further. Following the invasion of Iraq in 2003, the Kurds have become more politically powerful and an importuned force in the politics of the state, which in turn is even more important than the demographic issues in the powerful symbol of Kirkuk. As a reaction, another demographic change has occurred with informal rapid urban growth represented by many Kurdish returnees following the new Kurd government policy of Kurdification. The demographic change is a layered and multi-faceted social interaction that in many ways makes the resolution of Kirkuk’s ethno-political tension difficult to achieve, particularly when this complex picture is coloured by the presence of immense quantities of oil reserves. This thesis used GIS and CA- Markov to examine Kirkuk City’s urban growth, the factors that influenced its development, the impact of socio-political conflict represented by ethnic conflict on urban growth, the reshaping of the Master Plan and the pattern of settlement development of the city. A model was developed to simulate the residential expansion based on ethno-political conflict areas for each ethnic group in order to answer the question: “Dose political transition based on ethnicity affect the shape of a city master plan?”. The findings of the study suggested that there are significant effects of ethno-political factors in urban growth and planning, as well as future trends. However, the effect of the other physical, environmental and socio economic factors were not strong as a determinant of social interaction and integration, and other non-spatial factors were more important. The ethno-political factors shaped the city’s Master Plan toward the north–eastern side of the city even though it was not recommended in the previous Master Plan. The findings visualised the shape of the future Master Plan based on ethnicity. According to all the above-mentioned factors, if the status of Kirkuk governorate is not settled politically, Kirkuk City’s planning pattern will continue to be heterogeneous. The findings have important policy implications to avoid the segregation of the society of Kirkuk City and will assist policy makers and urban planners to consider the trends in urban growth expansion and give the advantages and consequences for each ethnic scenario.